2017
DOI: 10.2174/1874294701710010035
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Examination of Invertase Activities in the Growing Tip of the Plant Root

Abstract: Background:A growing part of the root is one of the most active sinks for sucrose coming from source leaves through the phloem. In the root, sucrose is unloaded from conducting bundles and is distributed among the surrounding cells. To be involved in the metabolism, sucrose should disintegrate into hexoses by means of degrading enzymes. Aims:The aim of this research was to explore the possibility of the involvement of one such enzymes, invertase, in phloem unloading as well as distribution of its activity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Suc metabolism could occur within the cytoplasm, with the Glc subsequently exported into the rhizosphere, or Suc could be first exported into the apoplast, where it could be hydrolyzed by cell wall invertases, leading to the release of Glc into the rhizosphere. Recently, Lunkova et al (2017) showed that maize roots have substantial vacuolar invertase activity in the region of cell elongation (∼2-7 mm from the root tip), with the highest activity in the cortical and epidermal cells, and that the activity was reduced in the meristem and more basal region of the roots. These results suggest that Suc is hydrolyzed within the symplasm and that Glc is released into the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Suc metabolism could occur within the cytoplasm, with the Glc subsequently exported into the rhizosphere, or Suc could be first exported into the apoplast, where it could be hydrolyzed by cell wall invertases, leading to the release of Glc into the rhizosphere. Recently, Lunkova et al (2017) showed that maize roots have substantial vacuolar invertase activity in the region of cell elongation (∼2-7 mm from the root tip), with the highest activity in the cortical and epidermal cells, and that the activity was reduced in the meristem and more basal region of the roots. These results suggest that Suc is hydrolyzed within the symplasm and that Glc is released into the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%